STRUKTUR KOMUNITAS PERIFITON DI SUNGAI BINGAI KOTA BINJAI SUMATERA UTARA Periphyton Community Structure in Bingai River, Binjai City, North Sumatera - Maria Christie Sembiring; Hasan Sitorus; Rusdi Leidonald (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2015)
Bingai River is a river which flow through the Binjai City, with length 15 km and large 150 km² in North Binjai area. The research aims were to know the community structure and relation of physical-chemical waters factors to periphyton community structure in Bingai River, Binjai City, North Sumatera. The research had been conducted in July to Agustus 2014. The research used Purposive Random Sampling method. Sampling was performed three times in three observation stations. Physical-chemical parameters and biological observed were temperature, pH, dissolved oxygen, brightness, current, nitrates, phosphates, diversity and abundance of periphyton. Based on the result obtained at three stations to consist of 34 genus divided to 3 class, that was Bacillariophyceae (23 genus), Chlorophyceae (8 genus), and Cyanophyceae (3 genus). Periphyton with the highest result in station 1 was Frustulia and the lowest result was Closterium, in station 2 the highest result was Navicula and the lowest was Terpsinoe, Skeletonema, Microspora, Fragilariforma, Oscillatoria, and Cosmarium, in station 3 the highest result was Navicula and the lowest was Terpsinoe. Periphyton Diversity (H´) ranged from 2,38 − 2,70. Abundance ranged from 10.136 − 30.216 ind/cm². Temperature averaged 28°C, pH ranged from 7,35 − 7,45, DO ranged from 4,65 − 4,75 mg/l, brightness ranged from 42,5 − 60 cm, current ranged from 0,15 − 0,21 m/det, nitrate ranged from 2,1 −2,55 mg/l, phosphate ranged from 0,18 − 0,25 mg/l. According to Diversity Index (H´) and physical-chemical factors Bingai River categorized as lightly polluted water.Keywords : Periphyton, Community Structure, Diversity, Abundance, Bingai River.